The Federal Criminal Code Is a Disgrace: Obstruction Statutes as Case Study - O'Sullivan, Julie R. (2006)
Any discussion of federal penal law must begin with an important caveat: There actually is no federal criminal code worthy of the name. A criminal code is defined as 'a systematic collection, compendium, or revision' of laws. What the federal government has is a haphazard grab-bag of statutes accumulated over 200 years, rather than a comprehensive, thoughtful, and internally consistent system of criminal law. In fact, the federal government has never had a true criminal code. The closest Congress has come to enacting a code was its creation of Title 18 of the United States Code in 1948. That exercise, however, accomplished little more than sweeping a host of internally-disorganized statutes containing fragmentary coverage into a series of chapters laid out in...alphabetical order. Readers should be cautioned, then, that the author's use of the term federal criminal code within this article is simply a shorthand for an incomprehensible, random and incoherent, duplicative, ambiguous, incomplete, and organizationally nonsensical mass of federal legislation that carries criminal penalties. To begin with the optimal, an effective and just system of penal laws should be: drafted by elected representatives to be as clear and explicit as possible so that citizens have fair notice of that which will subject them to criminal sanction; public; accessible; comprehensive; internally consistent; reasonably stable; rationally organized to avoid redundancy and ensure appropriate grading of offense seriousness; prospective only in application; and capable of uniform, non-arbitrary, and nondiscriminatory enforcement. No code drafted by human beings and produced by political institutions can meet all of these criteria. What is shameful about the state of federal penal law, however, is that none of these characteristics can be claimed by our code and our elected officials have made no serious effort to correct that glaring fact for decades. The author attempts to substantiate this proposition generally in part I and particularly in part II's examination of certain federal obstruction of justice statutes. Although previous code reform efforts in the 1960's through the 1980's failed, they did yield something that made the deficiencies of the substantive code more tolerable: the U.S. Sentencing Guidelines. Explained at greater length in part III, in pre-Guidelines practice, judges had vast discretion in sentencing criminal offenders; their choice of sentence was constrained only by the statutory maximum Congress set for the offense of conviction (e.g., 0-10 years). Because prosecutors often could choose among a variety of overlapping charges, many of which carried different statutory maximums, prosecutors' discretionary charging choices greatly affected the defendant's sentencing exposure